Microfinance Credit and Financial Performance of Small and Medium Enterprises in Nairobi City County - Kaboka , Nelson; Ndende, Fredrick W.S. (Journal of Finance and Accounting, 2023)
The study examined the impact of microfinance credit the financial performance of SMEs situated in Nairobi CBD. The research employed a cross-sectional descriptive survey methodology and focused on business owners and managers of SMEs located in the Nairobi CBD. The licensing department of Nairobi City County in 2017’s data informed the sample selection process. The researchers utilized a stratified random sampling methodology in order to include 70 individuals in the investigation. The primary instrument employed for data collection was a semi-structured questionnaire. The research was carried out utilizing SPSS 25.0, which encompassed the application of both descriptive and inferential statistical methods. The researchers employed a multivariate linear regression model to assess the variable’s statistical significance. The findings of the analysis were graphically represented through the utilization of tables and bar charts. The study’s coefficient was 0.631, accompanied by an adjusted R-squared value of 0.606. Both of these values were determined to have statistical significance with 95% CI. The findings of this research indicate that several factors, such as collateral security, loan-income ratio, branch penetration, and credit rating, collectively account for 63.1% of the variability SMEs performance in the Nairobi CBD. The findings of the study indicate that the inclusion of collateral security has a significant impact on performance (β = 0.251, p = 0.014 < 0.05). In a similar manner, it was found that the ratio of loans to income and the level of branch penetration had a statistically significant positive effect on financial performance (β = 0.238, p = 0.024 < 0.05; β = 0.382, p = 0.004 < 0.05, respectively). However, the study indicated that there was a positive trend in association between credit rating and SME performance. However, this trend was not statistically significant (β = 0.022, p = 0.844 > 0.05). This study draws a conclusion based on the empirical evidence provided, suggesting that collateral security has a significant and beneficial influence on SMEs performance in Nairobi CBD. Furthermore, the sustainability of small and medium companies (SMEs) inside the Central Business District of Nairobi is contingent upon some essential aspects pertaining to microfinance funding. Additionally, they should engage in thorough pre-loan planning and steadfastly adhere to their initial strategies in order to augment their financial performance. Keywords: Microfinance, Credit, Financial Performance, Small and Medium Enterprises (SMEs), Nairobi City County